Effects of rumen-protected or unprotected Clostridium butyricum on growth performance, rumen fermentation, immunity and antioxidation in fattening goats - Caixia Zhang; Jiyu Han; Hairong Wang (PLoS ONE, 2025)
Probiotics have been suggested to promote growth and immune performance in animals through long-term feeding. Among probiotics, Clostridium butyricum (C. butyricum) has been shown to have varying effects on the growth of ruminants. However, the impact of rumen-protected C. butyricum on ruminant organisms remains unclear. This study aimed to investigate the effects of rumen-protected and rumen-unprotected C. butyricum on the growth and plasma metabolites of fattening goats after lipopolysaccharide (LPS) challenge. A total of 24 fattening goats, aged 7–8 months, were randomly assigned to one of the following treatments: (1) control (CON); (2) unprotected C. butyricum (CB); and (3) rumen-protected C. butyricum (RPCB). After a 10-week feeding experiment (including two weeks of preparatory experiments), the goats were injected subcutaneously with LPS (1 μg/kg BW). The three treatments did not significantly affect growth performance, digestibility, or antioxidant enzyme activity (P > 0.05). However, the RPCB group showed a greater ability to reduce propionic acid (35.8%) in the rumen (P < 0.01) than did the CB group, thus alleviating the decrease in rumen pH (CB = 5.93, RPCB = 6.13, P < 0.01). Furthermore, the β-oxidation products in the plasma increased in both the CB and RPCB groups (P < 0.01). The difference in the fecal flora between the CB and RPCB groups was limited, but the content of harmful bacteria in the feces of the other two groups decreased compared with that in the CON group (P < 0.01). Unprotected C. butyricum increased the concentration of IgM after LPS injection (P < 0.01). 8-Amino-7-oxononanoate (KAPA) can serve as a biomarker for the effect of C. butyricum on the body. Overall, although rumen-protected C. butyricum could alleviate the decrease in rumen pH, our results suggest that direct feeding of C. butyricum could help improve the immune performance of fattening goats.